NEEDS AND MOTIVATIONS OF THE MAIN CHARACTER IN NETFLIX'S THE IN BETWEEN - Pricillia, Esther; Saraswati, Listya Ayu (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2023)
The study aimed to analyze the needs and motivations of the main character, Tessa, in Netflix's movie The In Between using the hierarchy of needs theory by Abraham Maslow. This study used descriptive qualitative methods to collect, describe, and summarize data. The study's primary goal was to examine how Tessa, the main character in The In Between, illustrates the hierarchy of human needs and motivations. The study focused on the main character's struggle to meet their psychological needs following personal life turmoil. The study's findings indicated that Tessa's character development aligned with Maslow's hierarchy of needs during the movie's narrative. Tessa's needs for love and belonging are the most dominant of the five hierarchy of needs she experiences.Keywords: hierarchy of needs, psychological needs, characterization, movie